EMBEDDED SYSTEMS WITH COMPONENT-BASED GPU SUPPORT: A STATE OF THE ART - MICLĂUȘ, Antoniu; PETRESCU, Șerban; VESCAN, Andreea (Studia Universitatis Babeș-Bolyai Informatica, 2019)
In order to deal with extremely large quantities of information, embedded systems need high capabilities in order to process the whole amount of data in real time. Two trends are present in the field: the usage of boards with Graphics Processing Units (GPUs) and the usage of component-based development (CBD). Components with GPU capabilities have the great advantage to be platform-independent. However, developing embedded systems with GPUs by using CBD was considered until very recently a problem with restricted availability and flexibility. By introducing specific GPU support for CBD in the form of flexible components and by improving their communication, a solution was identified and checked. Present paper aims to present a state-of-the-art and highlights the newest knowledge to date, articulating encountered confronted issues and describing existing solution approaches.